Diversification Benefits in Malaysia Real Estate Investment Trusts (M-REITs): Analysis by Property Types - Chien, Tay Chu; Mohd Diah, Mohd Lizam (Research in Management of Technology and Business, 2020)
Real Estate Investment Trusts (REITs) is a collective investment scheme that pooled fund and reinvests it mainly in real estate markets. Modern Portfolio Theory (MPT) stated that through diversification of the portfolio, a fund could maximise investment returns while minimising the corresponding risks related to specific investments. In this sense, REITs seem to fit the bill for investors that need to diversify their real estate investment portfolio while minimising risk related to direct investment in the physical property market. In Malaysia, there are different types of REITs that investors may consider invested in, from diversifying REITs to REITs that its investment portfolio specific to a property type. However, there are limited numbers of studies that look into the performance of each REITs company in Malaysia. This paper aims to evaluate the performance of M-REITs based on its asset composition in which the evidence of diversification benefit can be established. This study analyses pricing data of nine M-REITs companies for a period between 2008 and 2015 using the co-integration method. The findings show that there is no significant long-run relationship among M-REITs companies suggesting that there exist diversification benefits in M-REITs investment portfolio.